The DN-PUBLIC framework for enhanced oral healthcare precision: a public health strategy for dynamic navigation integration—a narrative review - Bhalerao, Ashwini; Kumar, Vaibhav (Frontiers in Oral Health, 2025)
Oral health disparities remain a pressing global concern, especially in communities with limited access to specialized dental care. Implant dentistry, while transformative for tooth replacement, often relies on techniques that can be imprecise, operator-dependent, and prone to complications. Dynamic Navigation (DN), a real-time computer-assisted technology, offers a promising solution by enhancing accuracy, reducing errors, and supporting minimally invasive procedures. This narrative review explores how DN can improve clinical precision, reduce surgical complications, and make implantology more accessible and cost-effective. It introduces the DN-PUBLIC framework—a strategic, public health-focused approach for integrating DN into broader healthcare systems, with a strong alignment to the United Nations Sustainable Development Goals (SDGs).A comprehensive review of current literature was conducted, assessing DN's impact on surgical safety, recovery outcomes, cost-efficiency, and its growing role in dental education. The findings highlight that DN significantly improves implant placement accuracy and reduces risks such as nerve injury or misalignment. By allowing for flapless procedures and better soft tissue preservation, DN leads to quicker recovery and greater patient comfort. Beyond clinical outcomes, DN enables general practitioners to perform complex procedures more confidently, expanding access to quality care in underserved regions. Economic analyses also suggest reduced operative time, fewer complications, and lower healthcare costs. In conclusion, DN has the potential to transform public oral health by improving outcomes, training, and access. The DN-PUBLIC framework offers a clear roadmap to guide ethical, inclusive, and sustainable integration of DN technology in dental practice worldwide.